Multimedia Technologies As An Element Of Development Of Modern Higher Education In Ukraine - Kharkivska, Alla; Ponomarova, Halyna (My University, 2021)
The article analyzes the use of multimedia technologies, with a personality-oriented, competence-based and systematic approaches and based on the principles of integrity, fundamentality, adaptability and variability. The organizational and pedagogical conditions for the use of multimedia technologies in teaching have been determined and substantiated. A criterion-evaluation toolkit has been developed for diagnosing the level of formation of the studied phenomena and to offer educational and methodological support for the learning process using multimedia technologies.
Kharkivska A. Multimedia Technologies As An Element Of Development Of Modern Higher Education In Ukraine / A. Kharkivska, H. Ponomarova // International Journal of Computer Science and Network Security. – 2021. – Vol. 21 № 10. – P. 145-148
Keywords: мультимедійні технології, комунікаційні технології, система освіти, навчальний процес; multimedia technologies, communication technologies, education system, educational process